2014
DOI: 10.1016/j.infbeh.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of others’ knowledge in French and Japanese children: A comparative study with a disambiguation task on 16–38-month-olds

Abstract: In order to explain the cultural differences reported in the results of false-belief tasks, we attempted to verify the 'task bias hypothesis' suggested by certain studies (e.g. Tardif et al. (2004). Journal of Child Language, 31, 779-800; Rubio-Fernandez & Geurts (2013). Psychological Science, 24(1), 27-33. doi 10.1177/0956797612447819). At the same time, we aimed to observe the theory of mind (ToM) ability of infants and young children under the age of three in verbal communication. To this end, we propose a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…Thus, the results of those tasks might be attributed to aspects of cognitive development other than false-belief understanding. In fact, several studies that have used simplified test settings showed that children passed first-order belief tasks earlier than previously proposed (Norimatsu, Blin, Hashiya, Sorsana, & Kobayashi, 2014;Onishi & Baillargeon, 2005;Southgate, Senju, & Csibra, 2007). The paradigm used in the current study reduced cognitive load by allowing observation of the event from the first-person perspective.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, the results of those tasks might be attributed to aspects of cognitive development other than false-belief understanding. In fact, several studies that have used simplified test settings showed that children passed first-order belief tasks earlier than previously proposed (Norimatsu, Blin, Hashiya, Sorsana, & Kobayashi, 2014;Onishi & Baillargeon, 2005;Southgate, Senju, & Csibra, 2007). The paradigm used in the current study reduced cognitive load by allowing observation of the event from the first-person perspective.…”
Section: Discussionmentioning
confidence: 83%
“…It would also feed the current debate about the importance of the verbal modality in ToM assessment: some ToM tasks, or some task items, rely indeed more than others on linguistic abilities, which might have led to an underestimation of ToM abilities in preschoolers (e.g. Norimatsu, Blin, Hashiya, Sorsana, & Kobayashi, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ne serait-ce que son propre prénom. Nous proposons ici un modèle pour les adultes mais nous espérons que sa confrontation avec les observations chez les enfants permettra de comprendre le processus de développement de la théorie de l'esprit dans le langage chez l'enfant (Norimatsu et al, 2014).…”
Section: Introductionunclassified